PENERAPAN SISTEM INTERNET VOTING PADA PELAKSANAAN PEMILU DI INDONESIA - Rezki Ayu Rahmawati; Yasmin Albaar; Dhiandra Pasha Valencia; Yohana Irmina Dola (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Digital transformation can bring about major changes in Indonesia's electoral process, which is an important part of democracy. The use of e-voting as part of digital transformation in election management in Indonesia is discussed in this paper. The purpose of this research is to study the ideas, advantages, and barriers of implementing e-voting. This research will also discuss the experiences of other countries that implement e-voting. In addition, this research will discuss the legal and regulatory context related to general elections in Indonesia, as well as legal issues related to the implementation of e-voting. In general elections, digital transformation is essential. Technology can improve vote counting efficiency, improve extensive infrastructure, improve public training and awareness, improve vote security, and improve socialization and communication. In addition, e-voting implementation faces technical issues such as adequate technological infrastructure, personnel training, vote security, and effective communication. To overcome these issues and ensure that e-voting goes well, a well-thought-out strategy is needed. The analysis and findings outlined include several suggestions for implementing e-voting in Indonesia. These include a clear legal framework, thorough infrastructure planning, public training and awareness, improved vote security, and better communication and socialization.